Kilfenora Cathedral, north wall, tomb niche, capital - O'Donovan, Danielle (My University, 2008)
Capital comprising: abacus, two rolls, angle fillet, scroll, bell with keel at mid-point, roll-and-fillet as necking. Simlar examples at Holycross, Kilconnell, Strade, Lorrah Dominican.
Tomb niche
Keywords: Architecture, Gothic -- Ireland; Kilfenora (Clare, Ireland); Funerary monuments; bell capitals; Late Medieval; keel moldings; roll moldings; roll-and-fillet moldings; fillets (moldings)